PENGARUH LINGKUNGAN KERJA, KERJASAMA TIM DAN STRES KERJA TERHADAP KINERJA KARYAWAN - Riha Fitria Ardelia; Ulfi Pristiana (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Performance at PT. Sinar Waringin Adikarya (SWA). This study uses a quantitative approach with multiple linear regression analysis methods to test the influence of independent variables (Work Environment, Teamwork, and Job Stress) on the dependent variable (Employee Performance). Data were collected through questionnaires distributed to employees of PT. Sinar Waringin Adikarya with a total of 40 respondents. The results of the study indicate that partially, Work Environment (X1) has a significant positive influence on Employee Performance, with a t-count value of 3.127 and a significant value of 0.003. Teamwork (X2) also has a significant positive influence, with a t-count value of 5.345 and a significant value of 0.000. Job Stress (X3) has a significant positive influence on Employee Performance, with a t-count value of 2.734 and a significant value of 0.010. Simultaneously, Work Environment, Teamwork, and Job Stress have a significant effect on Employee Performance, as evidenced by the calculated F value of 101.672 and the significant F value of 0.000. This study concludes that the three variables, both individually and together, contribute significantly to improving employee performance. These findings provide recommendations for the management of PT. Sinar Waringin Adikarya to create a conducive work environment, strengthen teamwork, and manage work stress effectively in order to improve overall employee performance.